Integration of Renewable Energy Sources to Operate in Microgrids in Rural Zones in Brazil - Bareta,Maria Luiza E. (2019)
Abstract In a world where technology is even more essential, quality and reliability of electrical system are fundamental. In Brazil, country where most of the energy is produced thought power plants, the existing distribution network is overwhelmed and the needs for the consolidation of distributed generation is growing. Wind and Solar power generation from biomass and another renewable sources are one alternative to power plants, which requires large areas and massive investment. The renewable energy sources mentioned may be assembled in a way to generate reliable energy to properties far from the cities, such as rural zones, where often energy from power plants doesn’t gets to. Distributed generation allows quick development of Brazilian farming and guarantees to the farmer independence from the energy dealerships. Microgrids assembled with renewable sources are one sustainable option and benefits Brazilian economy and society.